Diazabicyclo analogues of maraviroc: synthesis, modeling, NMR studies and antiviral activity12. Issue 2 (11th January 2017) - Legnani, L.; Colombo, D.; Venuti, A.; Pastori, C.; Lopalco, L.; Toma, L.; Mori, M.; Grazioso, G.; Villa, S.
Abstract : Two diazabicyclo analogues of maraviroc, in which the azabicyclooctane moiety is replaced by diazabicyclooctane or diazabicyclononane, were synthesized and tested, through a viral neutralization assay, on a panel of six pseudoviruses. Abstract : Two diazabicyclo analogues of maraviroc, in which the azabicyclooctane moiety is replaced by diazabicyclooctane or diazabicyclononane, were synthesized and tested, through a viral neutralization assay, on a panel of six pseudoviruses. The diazabicyclooctane derivative maintained a significant infectivity reduction power, whereas the diazabicyclononane was less effective. Biological data were rationalized through a computational study that allowed the conformational preferences of the compounds to be determined and a correlation between the inhibitory activity, the bridge length of the bicycle, and the rotational barrier around dihedral angle τ 7 to be hypothesized. A high-field NMR analysis supported the modeling results.